20:20 Hindsight. Retrofitting research relevance to the University Art Collections at Trinity College Dublin. - GILTRAP, CATHERINE (My University, 2010)
This paper considers the role of university art collections as meaningful contributors to the achievement of institutional goals relating to excellence in research, teaching and outreach. The discussion takes as its focus The University of Dublin, Trinity College, established in 1592, providing undergraduate and postgraduate courses in a wide range of disciplines. As practical fine art courses are not part of the teaching agenda, the university?s art collections have evolved mainly as a historical narrative of the significant figures and achievements of its parent institution, parallel to the core business of research and teaching. While the other academic collections at the university, from anatomy to zoology, were generated by object based learning, it was only from 1959 onwards that the art collections were actively developed and exploited as a catalyst for informal learning and interdisciplinary engagement, driven by the actions of one man in particular, the late George W. P. Dawson, genetics professor. 20:20 hindsight ? or the clearer perception of the significance of events after they have occurred ? has been used as a guiding principle for the present renaissance of the utility of the art collections. The author, as curator of the Art Collections, has taken inspiration from the actions of George Dawson to prepare to retrofit formal systems of meaningful associations between the art collections and research and teaching. In an era that requires clear correlations between demands on funding and fulfilling campus-wide strategic objectives, university art collections such as at Trinity College Dublin are becoming more formally integrated into academic programmes as the useful educational and interpretive tools that many have been on standby to be for centuries.
PUBLISHED
Keywords: university art collection; university heritage; cultural heritage; modern art; contemporary art; portrait collection; public sculpture; picture hire scheme; trinity college dublin; university curator